2008
DOI: 10.1186/1475-2875-7-220
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine-resistant Plasmodium vivax malaria in Debre Zeit, Ethiopia

Abstract: Background: Plasmodium vivax accounts for about 40% of all malaria infection in Ethiopia. Chloroquine (CQ) is the first line treatment for confirmed P. vivax malaria in the country. The first report of CQ treatment failure in P. vivax was from Debre Zeit, which suggested the presence of chloroquine resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 29 publications
5
84
1
1
Order By: Relevance
“…Although P. vivax resistance to CQ has been reported from several parts of the world, mainly Asia and South America, 12, 13 a report on confirmed P. vivax resistance from Ethiopia is quite recent, and the findings from this study further confirm CQ resistance reported in two other recent studies. 14,15 It is not known if the recurrent parasitemia cases detected in this study were caused by relapse, recrudescence, or reinfection. Based on the Indonesian experience, it has been suggested that failures after CQ therapy until day 16 are almost always caused by recrudescence, whereas failure between day 17 and 28 may be caused by recrudescence, reinfection, or relapse.…”
Section: Discussionmentioning
confidence: 88%
“…Although P. vivax resistance to CQ has been reported from several parts of the world, mainly Asia and South America, 12, 13 a report on confirmed P. vivax resistance from Ethiopia is quite recent, and the findings from this study further confirm CQ resistance reported in two other recent studies. 14,15 It is not known if the recurrent parasitemia cases detected in this study were caused by relapse, recrudescence, or reinfection. Based on the Indonesian experience, it has been suggested that failures after CQ therapy until day 16 are almost always caused by recrudescence, whereas failure between day 17 and 28 may be caused by recrudescence, reinfection, or relapse.…”
Section: Discussionmentioning
confidence: 88%
“…The emergence of resistance to CQ and the failing efficacy of PQ regimens in preventing relapses have raised great concerns in the control of P. vivax malaria. 9,10 Clinical CQ-resistant (CQR) P. vivax was first reported from Papua New Guinea in 1989, 11,12 followed by multiple reports from Indonesia, [13][14][15] Myanmar, 16,17 India, 18,19 Guyana, 20 Brazil, 21,22 Colombia, 23 and more recently in Ethiopia 24 and South Korea. 25 Continued surveillance of P. vivax drug resistance may detect CQR P. vivax parasites in most of its geographic range.…”
Section: Introductionmentioning
confidence: 99%
“…An updated search of available literature identified 231 titles, of which two RCTs) [18,19], 15 one-arm in vivo drug efficacy studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], and four prospective observational studies [35][36][37][38] were deemed eligible included in this analysis came from individual treatment programmes across Ethiopia and reported treatment outcomes for a range of 69 [35] to 487 patients [26]. One unpublished Master's thesis dissertation [36] was included and the rest were published in scientific journals [18-35, 37, 38].…”
Section: Resultsmentioning
confidence: 99%
“…It revealed significant differences between the lowquality studies (86.1%, 95% CI 69.7-102.6, p = <0.001, I 2 = 99.35%) [20,26,28,30,32,33,35,38] and high quality studies (96.9%, 95% CI 95.4-98.3, p < 0.001; I 2 = 81.7%) [18, 19, 21-25, 27, 29, 31, 36, 37]. Publication bias was also assessed using a funnel plot (Additional file 4).…”
Section: Quality Assessment and Sensitivity Analysismentioning
confidence: 94%
See 1 more Smart Citation